Secure And Fragile Watermarking Of Medical Images With Fingerprint Based Biometric Data Using Matlab - et. al., Geetha Priya S, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the modern era, the Internet has turn out to be the primary hub for exchanging information among users. At the same time, data attacks and threats may override the safety of these digital information. Many techniques like watermarking and digital signature are employed to protect these types of information in the field of data processing. Watermarking strategies are carried out in various fields that allows you to guard the content material from unauthorized user. It also assures the user on fact integrity and authenticity, patent evidence and content ownership.Robust watermarking strategies intent to show the patent and the proprietor issues. These strategies have the cap potential to withstand against malware issues like image compression, noise, and change in dimension, etc. However, semi-fragile watermarking, which is also called as soft authenticate, tries to exhibit only the integrity and accuracy of thematerial. This method cannot withstand against the malware attacks.